Pediatric robotic urologic surgery-2014 - James T Kearns; Mohan S Gundeti (Wolters Kluwer Medknow Publications, 2014)
We seek to provide a background of the current state of pediatric urologic surgery including a brief history, procedural outcomes, cost considerations, future directions, and the state of robotic surgery in India. Pediatric robotic urology has been shown to be safe and effective in cases ranging from pyeloplasty to bladder augmentation with continent urinary diversion. Complication rates are in line with other methods of performing the same procedures. The cost of robotic surgery continues to decrease, but setting up pediatric robotic urology programs can be costly in terms of both monetary investment and the training of robotic surgeons. The future directions of robot surgery include instrument and system refinements, augmented reality and haptics, and telesurgery. Given the large number of children in India, there is huge potential for growth of pediatric robotic urology in India. Pediatric robotic urologic surgery has been established as safe and effective, and it will be an important tool in the future of pediatric urologic surgery worldwide.